Implantação do Sistema Integrado de Gestão (SIG) na UFPB: um estudo de caso. - Araujo, Emerson Diego da Costa (2013)
Information technology has become a critical success factor for companies increasingly dependent on information . This work has as main goal to present the experience of deploying an Integrated Management System ( SIG ) , acquired from the Universidade Federal do Rio Grande do Norte Federal University of Paraíba . The SIG is composed of three main systems : Integrated Management of Academic Activities ( SIGAA ) Integrated Heritage Management, and Contract ( SIPAC ) , Integrated Human Resource Management ( SIGRH ) and the Integrated Administration ( SIGAdmin ), which supports the aforementioned systems . Each contains several modules designed to support the business processes of an administrative and academic institution. This work also describes the methods that were made , based on best practice standards , to provide effective and efficient program implementation . The main problems will be exposed , as well as the benefits from the implementation . With modules already deployed , UFPB is already able to give more flexibility to some processes needed to support the main activities of the institution , and also use a complete tool , able to help in decision-making by senior managers and directors and thus influence , in a positive way , within the context of greater agility and transparency of administrative and academic processes that support them , the lives of thousands of people who , somehow , are related to the institution .